Influence of neuroendocrine tumor cells on proliferation in prostatic carcinoma - Grobholz, Rainer; Griebe, Martin; Sauer, Christian; Michel, Maurice Stephan; Trojan, Lutz; Bleyl, Uwe (Human pathology, 2005)
Neuroendocrine (NE) tumor cells in prostatic carcinoma (PCa) may influence tumor proliferation by a paracrine stimulus. The role of NE tumor cells is discussed controversially. This study investigates the influence of NE tumor differentiation on proliferation in PCa. Neuroendocrine differentiation, Ki-67, and Polo-like kinase 1 were studied immunohistochemically in 73 consecutive prostatectomies. Polo-like kinase 1 (PLK1) expression was also studied by Western and Northern blot analysis. Tumors were classified as high NE (HNE) and low NE differentiated (LNE), and depending on the growth pattern, with solitary and clusters of NE tumor cells. Low NE differentiated tumors were defined as less than 30 and HNE as 30 or more NE tumor cells per hot spot. Patients were followed by serum prostate-specific antigen (PSA) analysis. Neuroendocrine differentiation was present at least focally in 70% of tumors; 57% were HNE and 43% LNE. Solitary NE tumor cells were more often found in low-grade PCa, whereas clusters of NE tumor cells were more frequent in high-grade PCa. PLK1 messenger RNA and protein as well as Ki-67 were overexpressed in tumor tissue compared with tumor-free tissue. A stronger proliferation as determined by Ki-67 and PLK1 expression was present in HNE tumors compared with LNE tumors and in tumors with clusters in contrast to tumors with solitary NE tumor cells. Analysis for PSA relapse-free survival showed an earlier progression in HNE than in LNE tumors and in PCa with clusters of NE tumor cells. A significant and clustered NE differentiation in PCa may lead to an increased proliferation and earlier tumor progression, whereas few and solitary NE tumor cells have no prognostic impact.